The Transmission System of the Greco-Arabic Translation Movement during the Abbasid Era and its Philosophical Contribution - Radya Cantika Suhardiman Putri; Febri Priyoyudanto (JUSPI (Jurnal Sejarah Peradaban Islam), 2023)
This study aims to determine the factors underlying the occurrence of the Greco-Arabic Translation Movement, how its process takes place, how the translation transmission system works, who are the figures behind it, and what its contributions are to the advancement of philosophy. This article uses the qualitative method through library research with data sources in the form of historical books written in the Abbasid dynasty, a book titled ‘Greek Thought, Arabic Culture’ by Dimitri Gutas, and articles related to the object of research. It can be concluded that the factors underlying the occurrence of the translation movement were the conquests by the Arabs, the Abbasid Revolution and the demography of Baghdad, and the pre-Abbasid translation movement. Based in Baghdad, this project lasted from the 8th century to the 10th century AD. The translation transmission system applied is the Greco-Syriac-Arabic translation. Some of the figures who played crucial roles in this project were caliph al-Mansur, caliph Harun ar-Rashid, caliph al-Ma’mun, Hunayn ibn Ishaq, the Banu Musa brothers, and Thabit ibn Qurra. This movement birthed the philosophy study. This project contributed to the advancement of philosophy both in classical and modern eras of Arab civilization and the world.